Outline of implemented eco-innovation activities - Hojnik, Jana (Organizacija (Kranj), 2014)
Background and Purpose: Providing a win-win situation for enterprises and the environment is raising the importance of eco-innovation. This article sheds light on the eco-innovation activities implemented within the clusters of the South Eastern European region (hereafter the SEE region). The main objective of this paper is to provide an outline of the situation pertaining to the implementation of eco-innovation activities in analyzed clusters. Methodology: Empirical evidence is provided through the performance of survey research with a sample of 52 clusters, encompassing 11 countries of the SEE region. The basic research method used in this research was a questionnaire developed for cluster organizations, with which we gathered the data and afterwards conducted descriptive statistics. Results: The findings demonstrate that the majority of analyzed clusters implement eco-innovation activities. The results indicate that 40 clusters out of 52 in all have set objectives with regard to eco-innovation support in their national or regional programs, followed by 35 clusters, which include objectives related to eco-innovation in their cluster strategies, and lastly, only 15 clusters are primarily focused on eco-innovation. Hence, our study depicting the current situation regarding the implementation of eco-innovation activities in analyzed clusters and clusters% orientation towards eco-innovation leads to us the discussion of why such differences in clusters occur. Conclusion: The huge differences related to the implementation of eco-innovation activities in clusters of the SEE region, can also reflect the level of the national/regional development in terms of economic indicators such as GDP and, at the same time, offer room for a lot of improvement, and an exchange of best practice.
Keywords: ecology; ekologija; inovcije; podjetništvo; podjetja; družbena odgovornost; jugovzhodna Evropa